Unintended transnationalism of Ukrainian military migrants in Poland: Socio-cultural aspect - Alina Burliai; Maryna Demianchuk; Oleksandr Burliai (Problems and Perspectives in Management, 2023)
The full-scale military invasion of Ukraine by the Russian Federation in 2022 triggered a massive wave of forced migration to Poland. This has resulted in the phenomenon of ‘unintended transnationalism.’ Transnational migrants do not part with their country of origin forever but live a double life, act as members of two socio-cultural communities and become carriers of a double culture. This study aims to systematize the socio-cultural peculiarities of the unintended transnationalism of military migrants from Ukraine to Poland.The theoretical foundations of migrants’ transnationalism are systematically analyzed and its main characteristics are systematized. The emergence of the so-called unintentional transnationalism of military migrants is revealed. A comparative analysis made it possible to compare transnational processes in Poland and Ukraine. The study found that migrants’ transnationalism is manifested through sharing their cultural values, traditions, and customs in a new cultural environment. The culture of migrants includes elements of the host country’s culture, elements of the culture of the migrants’ homeland, as well as new elements arising from the interaction of these two cultures. The main manifestations of migrants’ culture are language and communication, education, religious practices, intercultural dialogue, relations between representatives of different cultures, and other aspects of their daily lives. The study has shown that the transnationalism of military migrants can generate various cultural processes, including multilingualism, hybridization, cultural diffusion, cultural preservation, and intercultural dialogue.